From Diagnostic‐Therapeutic Pathways to Real‐World Data: A Multicenter Prospective Study on Upfront Treatment for EGFR‐Positive Non‐Small Cell Lung Cancer (MOST Study). (7th March 2019) - Pasello, Giulia; Vicario, Giovanni; Zustovich, Fable; Oniga, Francesco; Gori, Stefania; Rosetti, Francesco; Bonetti, Andrea; Favaretto, Adolfo; Toso, Silvia; Redelotti, Roberta; Santo, Antonio; Bernardi, Daniele; et al.
Abstract: Introduction: Gefitinib, erlotinib, and afatinib represent the approved first‐line options for epidermal growth factor receptor ( EGFR )‐mutant non‐small cell lung cancer (NSCLC). Because pivotal trials frequently lack external validity, real‐world data may help to depict the diagnostic‐therapeutic pathway and treatment outcome in clinical practice. Methods: MOST is a multicenter observational study promoted by the Veneto Oncology Network, aiming at monitoring the diagnostic‐therapeutic pathway of patients with nonsquamous EGFR ‐mutant NSCLC. We reported treatment outcome in terms of median time to treatment failure (mTTF) and assessed the impact of each agent on the expense of the regional health system, comparing it with a prediction based on the pivotal trials. Results: An EGFR mutation test was performed in 447 enrolled patients, of whom 124 had EGFR mutation and who received gefitinib ( n = 69, 55%), erlotinib ( n = 33, 27%), or afatinib ( n = 22, 18%) as first‐line treatment. Because erlotinib was administered within a clinical trial to 15 patients, final analysis was limited to 109 patients. mTTF was 15.3 months, regardless of the type of tyrosine kinase inhibitor (TKI) used. In the MOST study, the budget impact analysis showed a total expense of €3, 238, 602.17, whereas the cost estimation according to median progression‐free survival from pivotal phase III trials was €1, 813, 557.88. Conclusion: Good regional adherence and compliance to the diagnostic‐therapeutic pathway defined for patients with nonsquamous NSCLC was shown. mTTF did not significantly differ among the three targeted TKIs. Our budget impact analysis suggests the potential application of real‐world data in the process of drug price negotiation. Abstract : MOST was a multicenter observational study by the Veneto Oncology Network that monitored the diagnostic‐therapeutic pathway of nonsquamous EGFR mutant non‐small cell lung cancer patients, using one of three recommended agents: gefitinib, erlotinib, or afatinib. Results are reported here.